2020
DOI: 10.3390/md18090439
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth In Silico Search for Cuttlefish (Sepia officinalis) Antimicrobial Peptides Following Bacterial Challenge of Haemocytes

Abstract: Cuttlefish (Sepia officinalis) haemocytes are potential sources of antimicrobial peptides (AMPs). To study the immune response to Vibrio splendidus and identify new AMPs, an original approach was developed based on a differential transcriptomic study and an in-depth in silico analysis using multiple tools. Two de novo transcriptomes were retrieved from cuttlefish haemocytes following challenge by V. splendidus or not. A first analysis of the annotated transcripts revealed the presence of Toll/NF-κB pathway mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…For example, the investigation of scorpion venoms led to the discovery of Hadrurin, Scorpine, Vejovine, StCT2, Pandinin 1, and Pandinin 2, which are effective antimicrobial peptides [ 19 , 20 , 21 , 22 , 23 ]. Similar studies also found antimicrobial peptides in snakes, spiders, bees, ants, centipedes, lugworms, wasps, and cuttlefish [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionsupporting
confidence: 52%
“…For example, the investigation of scorpion venoms led to the discovery of Hadrurin, Scorpine, Vejovine, StCT2, Pandinin 1, and Pandinin 2, which are effective antimicrobial peptides [ 19 , 20 , 21 , 22 , 23 ]. Similar studies also found antimicrobial peptides in snakes, spiders, bees, ants, centipedes, lugworms, wasps, and cuttlefish [ 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionsupporting
confidence: 52%
“…To complete the analysis and search for peptides with low sequence homology such as piscidins, we used the homemade software program PepTraq [ 65 , 87 , 88 ]. The strategy developed to search for new piscidins was to use the sequence homologies observed at the signal peptide level of the precursors encoding piscidins.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike BLAST, such methods do not require the detection of sequence homology for the identification of candidate HDP, relying on the identification of primary sequence features shared by a training set of peptides with known antimicrobial activity, but uncommon in peptides with other biological functions. While an in-depth overview of these methods goes beyond the scope of this review (for a comprehensive description, see [58][59][60]), several recent publications showcase the potential of machine learning approaches in the discovery of novel HDP in non-model invertebrates [61][62][63]. It is however important to remark that no matter the level of sophistication that the current computational approaches utilize, laboratory functional validation remains a fundamental confirmatory step for any candidate HDP.…”
Section: Computation Approaches For the Discovery Of Novel Helminthic...mentioning
confidence: 99%